The Past Half Century of Engineering--And a Look Forward: Summary of a Forum - National Academy of Engineering (The National Academies Press, 2015)
Engineering is poised to make an even greater contribution to society in the next half century than it has made in the past half century. At its annual meeting on September 28-29, 2014, the National Academy of Engineering celebrated the 50th anniversary of its founding. A highlight of the meeting was a forum of distinguished speakers who considered the achievements of the last 50 years and looked toward the potential achievements of the next 50. The Past Half Century of Engineering - and a Look Forward summarizes their presentations.
Keywords: Engineering and Technology

An Assessment of the National Institute of Standards and Technology Material Measurement Laboratory: Fiscal Year 2014 - National Research Council (The National Academies Press, 2015)
The National Institute of Standards and Technology's (NIST's) Material Measurement Laboratory (MML) is our nation's reference laboratory for measurements in the chemical, biological, and materials sciences and engineering. Staff of the MML develop state-of-the-art measurement techniques and conduct fundamental research related to measuring the composition, structure, and properties of substances. Tools that include reference materials, data, and measurement services are developed to support industries that range from transportation to biotechnology and to address problems such as climate change, environmental sciences, renewable energy, health care, infrastructure, food safety and nutrition, and forensics. This report assesses the scientific and technical work performed by NIST's Material Measurement Laboratory. In particular, the report assesses the organization's technical programs, the portfolio of scientific expertise within the organization, the adequacy of the organization's facilities, equipment, and human resources, and the effectiveness by which the organization disseminates its program outputs.
Keywords: Engineering and Technology

Memorial Tributes: Volume 19 - National Academy of Engineering (The National Academies Press, 2015)
This is the 19th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964.
Keywords: Biography and Autobiography

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2014 Symposium - National Academy of Engineering (The National Academies Press, 2015)
This volume presents papers on the topics covered at the National Academy of Engineering's 2014 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2014 symposium was held September 11-13 at the National Academies Beckman Center in Irvine California. The topics covered at the 2014 symposium were: co-robotics, battery materials, technologies for the heart, and shale gas and oil. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.
Keywords: Engineering and Technology

Peer Review and Design Competition in the NNSA National Security Laboratories - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The National Nuclear Security Administration (NNSA) is responsible for providing and maintaining the capabilities necessary to sustain a safe, secure, and reliable nuclear weapons stockpile for the nation and its allies. Major responsibility for meeting the NNSA missions falls to the three NNSA laboratories: Los Alamos National Laboratory (LANL), Lawrence Livermore National Laboratory (LLNL), and Sandia National Laboratories (SNL). The NNSA National Security Laboratories contribute to that goal by maintaining the skills and capabilities necessary for stewardship of a reliable nuclear stockpile and also by maintaining a high level of technical credibility, which is a component of the nuclear deterrent. Since 1992 it has been U.S. policy not to conduct explosion tests of nuclear weapons. The resulting technical challenges have been substantial. Whereas a nuclear test was in some sense the ultimate "peer review" of the performance of a particular NEP design, the cessation of nuclear testing necessitated a much greater reliance on both intralab and interlab expert peer review to identify potential problems with weapon designs and define the solution space. This report assesses the quality and effectiveness of peer review of designs, development plans, engineering and scientific activities, and priorities related to both nuclear and non-nuclear aspects of nuclear weapons, as well as incentives for effective peer review. It also explores how the evolving mission of the NNSA laboratories might impact peer review processes at the laboratories that relate to nuclear weapons.
Keywords: Policy for Science and Technology; Conflict and Security Issues

Aligning the Governance Structure of the NNSA Laboratories to Meet 21st Century National Security Challenges - National Research Council (The National Academies Press, 2015)
Aligning the Governance Structure of the NNSA Laboratories to Meet 21st Century National Security Challenges is an independent assessment regarding the transition of the National Nuclear Security Administration (NNSA) laboratories - Los Alamos National Laboratory, Lawrence Livermore National Laboratory, and Sandia National Laboratories - to multiagency, federally funded research and development centers with direct sustainment and sponsorship by multiple national security agencies. This report makes recommendations for the governance of NNSA laboratories to better align with the evolving national security landscape and the laboratories' increasing engagement with the other national security agencies, while simultaneously encouraging the best technical solutions to national problems from the entire range of national security establishments. According to this report, the Department of Energy should remain the sole sponsor of the NNSA laboratories as federally funded research and development centers. The NNSA laboratories will remain a critically important resource to meet U.S. national security needs for many decades to come. The recommendations of Aligning the Governance Structure of the NNSA Laboratories to Meet 21st Century National Security Challenges will improve the governance of the laboratories and strengthen their strategic relationship with the non-DOE national security agencies.
Keywords: Conflict and Security Issues

Review Criteria for Successful Treatment of Hydrolysate at the Pueblo Chemical Agent Destruction Pilot Plant - National Research Council (The National Academies Press, 2015)
One of the last two sites with chemical munitions and chemical materiel is the Pueblo Chemical Depot in Pueblo, Colorado. The stockpile at this location consists of about 800,000 projectiles and mortars, all of which are filled with the chemical agent mustard. Under the direction of the Assembled Chemical Weapons Alternative Program (ACWA), the Army has constructed the Pueblo Chemical Agent Destruction Pilot Plant (PCAPP) to destroy these munitions. The primary technology to be used to destroy the mustard agent at PCAPP is hydrolysis, resulting in a secondary waste stream referred to as hydrolysate. PCAPP features a process that will be used to treat the hydrolysate and the thiodiglycol - a breakdown product of mustard - contained within. The process is a biotreatment technology that uses what are known as immobilized cell bioreactors. After biodegradation, the effluent flows to a brine reduction system, producing a solidified filter cake that is intended to be sent offsite to a permitted hazardous waste disposal facility. Water recovered from the brine reduction system is intended to be recycled back through the plant, thereby reducing the amount of water that is withdrawn from groundwater. Although biotreatment of toxic chemicals, brine reduction, and water recovery are established technologies, never before have these technologies been combined to treat mustard hydrolysate. At the request of the U.S. Army, Review Criteria for Successful Treatment of Hydrolysate at the Pueblo Chemical Agent Destruction Pilot Plant reviews the criteria for successfully treating the hydrolysate. This report provides information on the composition of the hydrolysate and describes the PCAPP processes for treating it; discusses stakeholder concerns; reviews regulatory considerations at the federal, state, and local levels; discusses Department of Transportation regulations and identifies risks associated with the offsite shipment of hydrolysate; establishes criteria for successfully treating the hydrolysate and identifies systemization data that should factor into the criteria and decision process for offsite transport and disposal of the hydrolysate; and discusses failure risks and contingency options as well as the downstream impacts of a decision to ship hydrolysate offsite.
Keywords: Conflict and Security Issues

Tying Flood Insurance to Flood Risk for Low-Lying Structures in the Floodplain - National Research Council (The National Academies Press, 2015)
Floods take a heavy toll on society, costing lives, damaging buildings and property, disrupting livelihoods, and sometimes necessitating federal disaster relief, which has risen to record levels in recent years. The National Flood Insurance Program (NFIP) was created in 1968 to reduce the flood risk to individuals and their reliance on federal disaster relief by making federal flood insurance available to residents and businesses if their community adopted floodplain management ordinances and minimum standards for new construction in flood prone areas. Insurance rates for structures built after a flood plain map was adopted by the community were intended to reflect the actual risk of flooding, taking into account the likelihood of inundation, the elevation of the structure, and the relationship of inundation to damage to the structure. Today, rates are subsidized for one-fifth of the NFIP's 5.5 million policies. Most of these structures are negatively elevated, that is, the elevation of the lowest floor is lower than the NFIP construction standard. Compared to structures built above the base flood elevation, negatively elevated structures are more likely to incur a loss because they are inundated more frequently, and the depths and durations of inundation are greater. Tying Flood Insurance to Flood Risk for Low-Lying Structures in the Floodplain studies the pricing of negatively elevated structures in the NFIP. This report review current NFIP methods for calculating risk-based premiums for these structures, including risk analysis, flood maps, and engineering data. The report then evaluates alternative approaches for calculating risk-based premiums and discusses engineering hydrologic and property assessment data needs to implement full risk-based premiums. The findings and conclusions of this report will help to improve the accuracy and precision of loss estimates for negatively elevated structures, which in turn will increase the credibility, fairness, and transparency of premiums for policyholders.
Keywords: Math, Chemistry, and Physics; Earth Sciences; Surveys and Statistics

Review Criteria for Successful Treatment of Hydrolysate at the Blue Grass Chemical Agent Destruction Pilot Plant - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
In 1993, the United States signed the Chemical Weapons Convention (CWC), an international treaty outlawing the production, stockpiling, and use of chemical weapons. The chemical weapons stockpiles at five of the U.S. chemical weapons storage sites have now been destroyed. At those sites, the munitions were robotically opened and the chemical agent was removed, collected, and incinerated.
Keywords: Environment and Environmental Studies; Conflict and Security Issues

2013-2014 Assessment of the Army Research Laboratory - National Research Council (The National Academies Press, 2015)
The National Research Council's Army Research Laboratory Technical Assessment Board (ARLTAB) provides biennial assessments of the scientific and technical quality of the research, development, and analysis programs at the Army Research Laboratory, focusing on ballistics sciences, human sciences, information sciences, materials sciences, and mechanical sciences. This report discusses the biennial assessment process used by ARLTAB and its five panels; provides detailed assessments of each of the ARL core technical competency areas reviewed during the 2013-2014 period; and presents findings and recommendations common across multiple competency areas.
Keywords: Conflict and Security Issues

Review of the 21st Century Truck Partnership: Third Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The 21st Century Truck Partnership (21CTP) works to reduce fuel consumption and emissions, increase heavy-duty vehicle safety, and support research, development, and demonstration to initiate commercially viable products and systems. This report is the third in a series of three by the National Academies of Sciences, Engineering, and Medicine that have reviewed the research and development initiatives carried out by the 21CTP. Review of the 21st Century Truck Partnership, Third Report builds on the Phase 1 and 2 reviews and reports, and also comments on changes and progress since the Phase 2 report was issued in 2012.
Keywords: Engineering and Technology; Energy and Energy Conservation